2019
DOI: 10.1186/s12879-019-3693-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and reliability of metrics to characterize types and sources of stigma among men who have sex with men and female sex workers in Togo and Burkina Faso

Abstract: Background Stigma is a multifaceted concept that potentiates Human Immunodeficiency Virus and sexually transmitted infection acquisition and transmission risks among key populations, including men who have sex with men (MSM) and female sex workers (FSW). Despite extensive stigma literature, limited research has characterized the types and sources of stigma reported by key populations in Sub-Saharan Africa. Methods This study leveraged data collected from 1356 MSM and 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 106 publications
(87 reference statements)
1
16
1
Order By: Relevance
“…Our study reported a high level of perceived and internalized homonegativity, as well as recent homonegative aggression and discrimination, which were declared in approximately one sixth of the study visits. This corroborates that same-sex behaviors are not well accepted socially [24,[40][41][42], although not illegal, except in Togo [43]. Our study suggests a temporal escalation in homonegative experiences, with greater discrimination leading to aggression.…”
Section: Social and Internalized Homonegativity And Violence With Womensupporting
confidence: 89%
“…Our study reported a high level of perceived and internalized homonegativity, as well as recent homonegative aggression and discrimination, which were declared in approximately one sixth of the study visits. This corroborates that same-sex behaviors are not well accepted socially [24,[40][41][42], although not illegal, except in Togo [43]. Our study suggests a temporal escalation in homonegative experiences, with greater discrimination leading to aggression.…”
Section: Social and Internalized Homonegativity And Violence With Womensupporting
confidence: 89%
“…Stigma measures were asked as attributable to engagement in sex work, except for measures of physical and sexual violence. Stigma measures were informed by a systematic review of stigma metrics and were validated with data from Togo and Burkina Faso 26,62,63 .…”
Section: Methodsmentioning
confidence: 99%
“…Seventeen studies reported on suicidal ideation [10,36,39,46,47,55,57,58,61,69,71,[75][76][77][78][79][80]. Most assessed suicidal ideation by asking about suicidal thoughts, for example, "have you thought about killing yourself?"…”
Section: Plos Medicinementioning
confidence: 99%